Influence of enzymatic hydrolysis conditions on the degree of hydrolysis and functional properties of protein hydrolysate obtained from Chinese sturgeon (Acipenser sinensis) by using papain enzyme. (April 2018) - Noman, Anwar; Xu, Yanshun; AL-Bukhaiti, Wedad Q.; Abed, Sherif M.; Ali, Abdelmoneim H.; Ramadhan, Abuubakar H.; Xia, Wenshui
Graphical abstract: Highlights: Protein hydrolysate was prepared from the muscles of Chinese sturgeon. Different factors were tested to determine the optimum extraction conditions. The degree of hydrolysis reached 24.89% under the optimum conditions. The yield was 17.47%, and the protein content of the hydrolysate was 79.67%. The solubility was between 86.57% and 98.74%, and the emulsifying activity index was between 11.0 and 13.27 m 2 /g. Abstract: In this study, protein hydrolysate was prepared from the muscles of Chinese sturgeon ( Acipenser sinensis ). The effects of different conditions on the degree of hydrolysis (DH) by using papain were investigated. The DH of 24.89% was attained under the optimum conditions including solid-to-liquid mixing ratio of 1:1, enzyme–substrate ratio of 3%, pH 6, temperature of 70 °C, and incubation time of 6 h. The yield of protein hydrolysate was 17.47%, in which the protein content was 79.67% and amino acid content was 96.35%. The molecular weight of peptides decreased with the progress in hydrolysis time. Protein hydrolysate solubility ranged between 86.57% and 98.74%, emulsifying activity index was 11.0–13.27 m 2 /g, emulsion stability index was >94% at different pH levels, water holding capacity was 1.93 g water/g protein, oil holding capacity was 2.59 g oil/g protein, and foam capacity was 76.67%. The obtained fish protein hydrolysate contains improved functional properties and has potential applications in food industries.